Aeolian sediment transport and deposition in a modern high‐latitude glacial marine environment. Issue 6 (21st March 2014) - Chewings, Jane M.; Atkins, Cliff B.; Dunbar, Gavin B.; Golledge, Nicholas R.
Abstract: Aeolian sand and dust in polar regions are transported offshore over sea ice and released to the ocean during summer melt. This process has long been considered an important contributor to polar sea floor sedimentation and as a source of bioavailable iron that triggers vast phytoplankton blooms. Reported here are aeolian sediment dispersal patterns and accumulation rates varying between 0·2 g m −2  yr −1 and 55 g m −2  yr −1 over 3000 km 2 of sea ice in McMurdo Sound, south‐west Ross Sea, adjacent to the largest ice free area in Antarctica. Sediment distribution and the abundance of southern McMurdo Volcanic Group‐derived glass, show that most sediment originates from the McMurdo Ice Shelf and nearby coastal outcrops. Almost no sediment is derived from the extensive ice free areas of the McMurdo Dry Valleys due to winnowed surficial layers shielding sand‐sized and silt‐sized material from wind erosion and because of the imposing topographic barrier of the north‐south aligned piedmont glaciers. Southerly winds of intermediate strength ( ca 20 m sec −1 ) are primarily responsible for transporting sediment northwards and offshore. The results presented here indicate that sand‐sized sediment does not travel more than ca 5 km offshore, but very‐fine sand and silt grains can travel >100 km from source. For sites >10 km from the coast, the mass accumulation rate is relatively uniform (1·14 ± 0·57 g m −2  yr −1 ), three orders of magnitude above estimated global atmospheric dust values for the region. This uniformity represents a sea floor sedimentation rate of only 0·2 cm kyr −1, well below the rates of >9 cm kyr −1 reported for biogenic‐dominated sedimentation measured over much of the Ross Sea. These results show that, even for this region of high‐windblown sediment flux, aeolian processes are only a minor contributor to sea floor sedimentation, excepting areas proximal to coastal sources.